The Chain of Business Failures Village Owned Enterprises Gain Profits and Create Community Welfare - Suwito Suwito; Abdullah W Jabid (Atestasi : Jurnal Ilmiah Akuntansi, 2022)
This study aims to uncover the chain of Village Owned Enterprises (BUMDes) business failures in the West Halmahera Regency. BUMDes business is a village government business that is run to achieve the goals of profit and society welfare. Empirical facts show that after the Village formed BUMDes and made a sizeable Equity Participation in BUMDes, what happened was that BUMDes BUMdes businesses experienced suspended animation. As a result, until now, the existence of BUMDes has not been able to contribute to Village Original Revenue and improve the welfare of rural communities as expected by the Village and the Community. The researcher uses a qualitative approach with the Transcendental Phenomenology method to achieve this goal. The research information includes elements of the village government, BUMDes managers, and village communities who have been in contact with BUMDes. The study results provide evidence that the failure of the BUMDes business is caused by the high conflict of interest of the village head and the indifference of the Village Consultative Body (BPD) towards BUMDes. This research contributes theoretically to the development of regional financial management science and information material for the West Halmahera Regency Government to make it easier for local governments to break the chain of failure of the BUMDes business.